A Study of Approximation Properties of Beta Type Summation-Integral Operator - Bhatt, Dhawal J.; Mishra, Vishnu Narayan; Jana, Ranjan Kumar (Discontinuity, Nonlinearity, and Complexity, 2026)
In the present paper we introduce Durrmeyer-type operator involving the beta function and Baskakov basis function and study its approximation properties. We obtain the rate of convergence in different terms. The uniform convergence of sequence of these operators is achieved using Korovkin’s theorem. Order of approximation for functions of some special class is also obtained. We establish the Voronovskaja type asymptotic result for this operator and a direct estimate of approximation for sequence of these operator.